2007
DOI: 10.1002/elan.200703922
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Cadmium, Lead, Copper, and Thallium in Highly Saline Samples by Anodic Stripping Voltammetry (ASV) Using Mercury‐Film and Bismuth‐Film Electrodes

Abstract: This paper describes a comparative study of the simultaneous determination of Cd(II), Pb(II), Tl(I), and Cu(II) in highly saline samples (seawater, hydrothermal fluids, and dialysis concentrates) by ASV using the mercury-film electrode (MFE) and the bismuth-film electrode (BiFE) as working electrodes. The features of MFE and BiFE as working electrodes for the single-run ASV determinations are shown and their performances are compared with that of HMDE under similar conditions. It was observed that the strippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 33 publications
0
35
1
2
Order By: Relevance
“…Subsequently, the stock supporting electrolyte solution (1.0 mL) was mixed with the sample. The initial pH value (6.2) was adjusted with a few drops of 25% (m/v) NH 4 OH solution. Deaeration interval of 300 s was used as prior starting the sequential method.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the stock supporting electrolyte solution (1.0 mL) was mixed with the sample. The initial pH value (6.2) was adjusted with a few drops of 25% (m/v) NH 4 OH solution. Deaeration interval of 300 s was used as prior starting the sequential method.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…In counterpart, the contamination source of thallium in DCs is potassium chloride (used in low concentrations) because thallium is a natural contaminant of potassium. 2,4 In fact, there are few available data about contaminants measured directly in formulations of DCs. However, in all cases (including the present paper) lead was found always in much higher concentrations than thallium.…”
Section: Thallium Cadmium Lead and Coppermentioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, we showed that the contamination of hemodialysis patients by toxic metals such as Al, As, Zn, Pb, Cd and Tl can be related to their presence in dialysis concentrates or water used for the preparation of dialysis fluids. [2][3][4][5][6][7][8][9] Besides, Lee and co-workers 1 reported that the contamination of hemodialysis patients could be also related to the medication used in the treatment of anemia, such as the renal antianemic human recombinant erythropoietin (EPO).…”
Section: Introductionmentioning
confidence: 99%